AVALIAÇÃO DA APLICAÇÃO DE JOGOS NA 6ª SÉRIE: EQUAÇÕES, INEQUAÇÕES E SISTEMAS DE EQUAÇÕES DO 1º GRAU - Uberti, Angelita (2011)
This research investigated the use of games as a resource for the teaching and learning of equations, systems of equations and inequalities of first degree. The work was developed with a group of 6th grade of elementary school, in a public school upstate Rio Grande do Sul. From the literature review based on research about games and algebra, as well as the analysis of textbooks used in elementary school for the teaching of equations, systems of equations and inequalities, games were built up, applied to 24 students at grade 6º of elementary school. The research is qualitative in nature and were employed, as instruments, a pre-test and notes of observations in a diary. Application of each of the games were analyzed and it was noticeable that there was better understanding about the content involved in the games. It is considered that the experience can be reapplied in other classes and then we elaborated a set of activities, in which games are presented, as well as suggestions for teachers. This set of activities is the product resulting from the dissertation.